Transformation Early Childhood Education in Iraq: Challenges, Innovations, and Future Prospects - Saro'i, Mohammad; Sain, Zohaib Hassan; Afriani, Gusma; Azizah, Suci Midsayhri; Rahma Pratiwi, Emy Yunita (Absorbent Mind, 2024)
The article "Transformation Early Childhood Education in Iraq: Challenges, Innovations, and Future Prospects" provides a comprehensive analysis of the current landscape of early childhood education (ECE) in Iraq. Through a systematic literature review methodology, the study identifies and examines the major challenges facing ECE in Iraq, including inadequate funding, shortage of qualified educators, and cultural barriers. Moreover, the research explores innovative approaches and promising initiatives aimed at revitalizing ECE in Iraq, such as community-driven projects, technology-enabled solutions, and government-led reforms. By synthesizing empirical evidence with theoretical frameworks and situating the research within the socio-political context of Iraq, the analysis offers valuable insights for informing evidence-based decision-making and practice in the field of early childhood education. The study concludes with recommendations for future research, emphasizing the need for longitudinal studies, intersectional analyses, and rigorous evaluations to drive meaningful change and foster equitable access to quality ECE for all children in Iraq.